1991
DOI: 10.1111/j.1365-3121.1991.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Subduction and eduction of continental crust: major mechanisms during continent‐continent collision and orogenic extensional collapse, a model based on the south Norwegian Caledonides

Abstract: During continental collision in the middle Silurian, the thickness of the lithosphere under the Caledonides of S. Norway was doubled by subduction of the western margin of Baltica, including the Western Gneiss Region, under Laurentia. Crustal rocks of the Baltic plate reached sub-Moho depths of near 100 km or more as inferred from the presence of coesite in eclogites. Isostatic calculations indicate an average elevation of the mountain chain of about 3 km at this stage. The subducted lithosphere experienced ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
253
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(265 citation statements)
references
References 43 publications
7
253
2
Order By: Relevance
“…By analogy with models for orogenic extensional collapse (Dewey, 1988;England and Houseman, 1988;Platt and England, 1994), it is conceivable that hinterland uplift and decompression by top-east extensional shear zones in the telescoped miogeocline, may have been a consequence of thinning of the mantle lithosphere as previously suggested (Andersen and Jamtveit, 1990;Andersen et al, 1991). This process would have increased the syn-orogenic surface slope, and it could also have reduced the dip of the sole thrust in the eastern parts of the orogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with models for orogenic extensional collapse (Dewey, 1988;England and Houseman, 1988;Platt and England, 1994), it is conceivable that hinterland uplift and decompression by top-east extensional shear zones in the telescoped miogeocline, may have been a consequence of thinning of the mantle lithosphere as previously suggested (Andersen and Jamtveit, 1990;Andersen et al, 1991). This process would have increased the syn-orogenic surface slope, and it could also have reduced the dip of the sole thrust in the eastern parts of the orogen.…”
Section: Discussionmentioning
confidence: 99%
“…A model suggesting that the initial extensional decompression of the hinterland eclogites in the Western Gneiss Region occurred contemporaneously with contractional tectonics in the foreland was put forward by Andersen et al (1991). The principal structures and fabrics in the exhumed deep-crustal rocks that have been related to the decompression of the lower plate rocks are: (1) by coaxial vertical shortening/horizontal stretching at eclogite-to amphibolite-facies conditions; and (2) by non-coaxial deformation related to extensional detachments and shear zones at amphibolite-to greenschist-facies conditions.…”
Section: Extensional Decompression Of the Lower Platementioning
confidence: 99%
“…Seismic profiles from the Archean age Baltic [BABEL Working Group, 1990] and Canadian [Henstock et al, 1998] shields suggested that they have been stable for over 1.5 Ga and still preserve their crustal roots as revealed by depressed Moho boundaries with significant relief. In contrast, Paleozoic orogens such as the Appalachians, Caledonides, and Variscides underwent post-orogenic collapse and extension as indicated by relatively flat and shallow Mohos and the wide Atlantic Ocean in between [Cook et aI., 1979;Meissner et aI., 1987;Nelson et aI., 1987;Andersen et al, 1991;Boundy et aI., 1992;Austrheim et aI., 1997].…”
mentioning
confidence: 99%
“…An increasing number of multidisciplinary studies of collisional zones and an abundance of geophysical data in the past years suggest that the composition and structure of the continental lower crust may play a critical role in the geodynamic development of mountain belts [Laubscher, 1990;Andersen et al, 1991;Dewey et aI., 1993;Platt and England, 1994;Baird et aI., 1996;Wernicke et al, 1996;Austrheim et al, 1997;Le Pichon et aI., 1997]. Of particular interest lately has been the metamorphic phase-change of the orogenic lower crust to eclogite facies rocks, as this process is being considered responsible for gravitational destabilization of orogenic belts.…”
mentioning
confidence: 99%
“…Smith 1984;Wang and Liou 1991). The argument was largely due to the rare preservation of the preversus post-metamorphic field relationships between eclogite and the host rocks, as well as retrograde overprinting of the host rocks that erased the evidence of UHP metamorphism (Andersen et al 1991;Zhang et al 1995). Numerous studies on the eclogite-bearing host rocks in these localities have shown that those rocks have in fact been subjected to coeval highpressure and UHP metamorphism (Wang and Liou 1991;Zhang et al 1995;Wain 1997;Carswell et al 2003;Liu et al 2005;Butler et al 2013), and hence they represent coherent slices of continental crust.…”
Section: Discussionmentioning
confidence: 99%